ANÁLISIS FINANCIERO PROSPECTIVO DE LA COOPERATIVA DE AHORRO Y CRÉDITO DE LA PEQUEÑA EMPRESA CACPE LOJA LTDA. PERIODO 2017-2022 - Sánchez Fuertes, Alexander Paul (2019)
The present titling work was developed with the objective of evaluating the efficiency and financial sustainability of the Cooperativa de Ahorro y Crédito de la Pequeña Empresa CACPE Loja Ltda., during the period 2017-2022. In this context, a literature review was carried out on the Popular and Solidarity Economy System worldwide, its adaptation in the country, evolution, control and financial evaluation methodologies. With regard to the methodology applied, different methods were used which facilitated the systematic and orderly performance of the degree work. As well as the scientific method that helped to compile information referring to the object of study, the deductive method that allowed to establish the situation of the entity based on international standards, with the inductive method the financial position of the entity was determined starting from its financial statements, the analytical method served to make the interpretation of the mentioned statements through the use of mathematical calculations. As part of the work, the CAMEL methodology was applied, on the basis of which it was determined that the entity has a high financial position (2.87 out of 5), which reflects the presence of weaknesses, but with the capacity to resolve them. In addition, projections were applied based on historical growth, strategic policies of the entity and the economic situation of the country to know the possible behavior of the financial indicators, in three possible scenarios (optimistic, trend, pessimistic), which were based on historical events, with the objective of recommending the directors to carry out a constant evaluation and correction of their activities, accompanied by the application of forecasts to know through indicators the possible financial stability, so as to establish corrective strategies that lead to the sustainable development of the organization. Assuming that the entity, through strengthening activities, manages to reduce its weaknesses to the minimum, it will grow at a rapid pace, due to the generation of profits and reduction of expenses, which according to the results is the main weakness of the cooperative.